Reconstructing special educators’ knowledge about families with members in the autistic spectrum through befriending experiences - Mavropoulou, Sophia; Padeliadu, Susana (International Journal about Parents in Education, 2023)
The role of parents within special education teacher preparation programs has been widely recognized. Traditional approaches for preparing special educators to interact with parents of children with special needs have been mainly classroom based promoting a narrow view of the disability, as a construct isolated from its micro-level social context (i.e., the home). Befriending has been increasingly supported as an emerging approach for the social support of vulnerable families in the community. Drawing upon the limitations of the traditional approaches and the need for reforming special education teacher training towards experiential learning and greater community engagement, in this paper we will share the insights from the development of a three-year befriending project between a university department and two charities of parents with members in the autistic spectrum. Overall, the scheme involved 35 families with persons in the autistic spectrum and 75 befrienders, the majority of which (n=60) were trainee special education teachers. Finally, we will discuss how befriending, viewed as a process for reconstructing special education teachers’ knowledge about families with persons in the autistic spectrum, can be embedded within curricula in special education teacher training programs.